A web-based intelligent tutoring system for a basic control course - Ozek, Muzeyyen Bulut; Akpolat, Zuhtu Hakan; Orhan, Ahmet (Wiley, 2013)
The most important feature of the intelligent tutoring systems (ITS), one of the most popular study topics of recent years, is that it provides an opportunity for individual learning by taking students' individual differences into account. In order to be able to realize this feature, it is necessary that the system recognizes students well. The process of recognizing student is performed as a result of observations which ITS applies on students. A number of uncertainties arise during these observations. In order to minimize learning uncertainties and create a productive and effective ITS, type-2 fuzzy logic, one of the artificial intelligence techniques, is used in the system developed in this study. In order to show the effectiveness of the developed web-based ITS, it is applied to the teaching of a basic Control Course. The educational evaluation of the system is presented in the paper. (c) 2011 Wiley Periodicals, Inc. Comput Appl Eng Educ 21: 561-571, 2013
Keywords: intelligent tutoring systems; individual learning; uncertainty; type-2 fuzzy logic